Engineering Education in 2015 (or Sooner) - Richard, M. Felder (2005)
An outcomes-based accreditation system for engineering programs was adopted in 2001 in the United States and is used by all full and provisional signatories of the Washington Accord. The system requires major transformations in the ways engineering curricula are structured, delivered, and assessed. As might be expected, many engineering staff members are less than enthusiastic about the proposed changes, arguing that the existing system has always functioned well and needs no radical revision. The ongoing debate involves four focal issues: (1) How should engineering curricula be structured? (2) How should engineering courses be taught and assessed? (3) Who should teach? (4) How should the teachers be prepared? This paper outlines the opposing positions on each of these issues' the traditional position, which has been the predominant approach in engineering education for the past five decades, and the alternative position, which is far more compatible with the requirements of the Washington Accord.